THE EFFECT OF SOCIAL INFLUENCE ON ICT USE BEHAVIOR AMONG MOMPRENEURS IN FASHION MSMES - Rania Ninda Triswanti; Kadiyono, Anissa Lestari; Rezki Ashriyana Sulistiobudi (Media Riset Bisnis & Manajemen, 2024)
The rapid development of digital technology has made the use of Information and Communication Technology (ICT) essential for running Micro, Small, and Medium Enterprises (MSMEs), especially for mompreneurs in the fashion sector. This study aims to analyze the impact of social influence on ICT use behavior in mompreneurs who run MSMEs in the fashion sector in Bandung City. The research method used is a quantitative non-experimental approach involving 102 respondents who met the research criteria. The results of the data analysis show that social influence has a significant and positive effect on ICT use behavior. Furthermore, the comparison analysis shows that there is a significant difference in social influence based on the respondent’s level of education. This finding explains that social influences significantly affect use behavior, especially in using ICT for entrepreneurship among mompreneurs.